2019
DOI: 10.1002/hep.30686
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia in Cirrhosis: Looking Beyond the Skeletal Muscle Loss to See the Systemic Disease

Abstract: Sarcopenia is a common complication of cirrhosis and is defined as a progressive and generalized loss of skeletal muscle mass, strength, and function. Sarcopenia is associated with poor prognosis and increased mortality. How sarcopenia and muscle wasting relate to such poor outcomes requires looking beyond the overt muscle loss and at this entity as a systemic disease that affects muscles of vital organs including cardiac and respiratory muscles. This review explores the pathophysiological pathways and mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
2
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 87 publications
1
64
2
5
Order By: Relevance
“…cirrhotic patients (16)(17)(18)(19)(20). In the present study, we showed that the physical data automatically estimated with the BIA method correlated well with the directly measured physical data and were related to the prognosis of the cirrhotic patients as well the directly measured anthropometric data.…”
Section: Discussionsupporting
confidence: 67%
“…cirrhotic patients (16)(17)(18)(19)(20). In the present study, we showed that the physical data automatically estimated with the BIA method correlated well with the directly measured physical data and were related to the prognosis of the cirrhotic patients as well the directly measured anthropometric data.…”
Section: Discussionsupporting
confidence: 67%
“…In patients with cirrhosis, Kazemi-Bajesti showed that sarcopenia was more prevalent in patients with low left ventricular mass [59]. Cardiac sarcopenia was recently defined by the loss of cardiomyocytes resulting in impaired cardiac function in the absence of any cardiovascular disease [60].…”
Section: Is Cardio-respiratory Sarcopenia Frequent In Patients With Cmentioning
confidence: 99%
“…Japanese CLD patients are aging these days, and it is also an important public health problem as aging can be associated with sarcopenia [10,11]. How sarcopenia is associated with such adverse clinical outcomes needs to be looked at beyond the overt muscle mass loss or muscle strength decline and at this clinical entity as a systemic disease [12][13][14]. Muscle mass has been assessed by different techniques such as the bioimpedance analysis (BIA), dual-energy X-ray, computed tomography (CT) and magnetic resonance imaging, and the functional consequence of sarcopenia is estimable by handgrip strength (HGS) or other more composite tests such as the walking test [10,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%